An initial investigation of preservice teachers in the United States and possible applications to Ukraine: perceived knowledge of response to intervention - Weishaar, Phillip M.; Fuchs, Wendy W.; Williams, Llena R. (Social Welfare: Interdisciplinary Approach, 2012)
Ukraine and the United States are engaged in education reform movements to improve quality of future teachers. Reform in the United States focuses on the use of evidence-based practices and data-based decision making. Reform in Ukraine focuses on democratic, learner-centered education. Using one university in the United States, this research investigates the degree to which preservice teacher candidates in different teacher training programs (early childhood, elementary, secondary, special education) perceive knowledge of components from the Response to Intervention model, a major focus of school reform. Application of the study to Ukraine is discussed.